Analytical Results of UV Absorbents in Cosmetics (April 2004 to March 2008) - TERAJIMA, Kiyoshi; SUZUKI, Atsuko; NAKAMURA, Yoshiaki; YOKOYAMA, Toshiro; OGINO, Shuzo; ITO, Koichi; HAMANO, Tomoko; MORI, Ken’ichiro; MIYAMOTO, Michiko (ChemoBio Integrated Management, 2010)
Analytical results of UV absorbents in 891 cosmetics collected at our center from April 2004 to March 2008 were sorted according to the type of cosmetics and ingredients. UV absorbents were detected in 133 samples. 2-Ethylhexyl p-methoxycinnamate (EMC) was detected most frequently (89 samples), followed by 4-tert-butyl-4&rsquo:-methoxydibenzoyl-methane (BMB) (26 samples), and 2-hydroxy-4-methoxybenzophenone (HMB) (26 samples). In sunscreen, UV absorbents were detected frequently, in 36 of 50 samples. In these samples, EMC was mainly observed, and its content was 1?10%. Thirteen of 18 samples of perfume and eau de cologne contained various ingredients besides BMB, and the content was 1% or less. There were a number of samples in which several UV absorbents were detected.